2013
DOI: 10.1371/journal.pone.0057925
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic Role of the MYH9/APOL1 Region on Familial Hematuria Genes

Abstract: Familial hematuria (FH) is explained by at least four different genes (see below). About 50% of patients develop late proteinuria and chronic kidney disease (CKD). We hypothesized that MYH9/APOL1, two closely linked genes associated with CKD, may be associated with adverse progression in FH. Our study included 102 thin basement membrane nephropathy (TBMN) patients with three known COL4A3/COL4A4 mutations (cohort A), 83 CFHR5/C3 glomerulopathy patients (cohort B) with a single CFHR5 mutation and 15 Alport syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…Previous genome-wide association studies have identified variants in the MYH9 and its closely linked APOL1 gene to confer major susceptibility towards ESRD in various types of renal diseases. 20 In the same Cypriot CFHR5 nephropathy cohort, we presented evidence for yet another putative modifier. 21 Specifically, a variant in the target site of miR-1207-5p in the 3 0 UTR of HBEGF was associated with severity of disease.…”
Section: Primary Mutations and Genetic Modifiers As Examples Of Psementioning
confidence: 70%
See 1 more Smart Citation
“…Previous genome-wide association studies have identified variants in the MYH9 and its closely linked APOL1 gene to confer major susceptibility towards ESRD in various types of renal diseases. 20 In the same Cypriot CFHR5 nephropathy cohort, we presented evidence for yet another putative modifier. 21 Specifically, a variant in the target site of miR-1207-5p in the 3 0 UTR of HBEGF was associated with severity of disease.…”
Section: Primary Mutations and Genetic Modifiers As Examples Of Psementioning
confidence: 70%
“…Exploiting several cohorts of patients with familial hematuria as a common finding, we showed association of “Severe” disease in CFHR5 nephropathy (a form of C3 glomerulopathy) with MYH9 variant rs11089788 that we confirmed in an independent cohort. Previous genome‐wide association studies have identified variants in the MYH9 and its closely linked APOL1 gene to confer major susceptibility towards ESRD in various types of renal diseases …”
Section: Primary Mutations and Genetic Modifiers As Examples Of Pseudmentioning
confidence: 99%
“…To date, these results have been verified by multiple groups [ 13 17 ]. The exact mechanisms for this adverse outcome remain unknown but the role of genetic modifiers has been implicated [ 18 22 ]. A significant feature of heterozygous COL4A mutations is the broad phenotypic heterogeneity, while the clinical outcome is at times better described as later-onset Alport-related nephropathy (LOAN) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, MYH9 variants have been shown to be predictive for kidney function in the general adult population [ 10 12 ] as well as in progression of primary [ 20 , 21 ] or secondary nephropathies [ 22 24 ]. Freedman et al were the first to denote potential MYH9 genotype impact on post-transplant FSGS relapse [ 25 ] while this study of ours investigates an association of MYH9 variants with eGFR and proteinuria in a setting of kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%